THE INFLUENCE OF INVESTMENT ON ECONOMIC GROWTH IN INDONESIA: ECONOMIC AND LEGAL PERSPECTIVES - Ardi Aprinawan Popi; Andi Azhar; Desy Ervitasari (Suluh Adiluhung Publisher (SAPub), 2025)
Investment plays an important role in encouraging Indonesia's economic growth. This study aims to analyze the influence of investment on economic growth in Indonesia. The research method used multiple regression analysis with secondary data from the Central Statistics Agency (BPS) and Bank of Indonesia for the 2010-2022 period. The results of the study show that investment has a significant influence on economic growth in Indonesia, with a contribution of 25% to GDP. Foreign direct investment and dose investment have a psychic influence on economic growth. Therefore, policies need to be implemented to increase investment and encourage national economic growth.